Lauren Holliday: capstone - Holliday, Lauren, artist (Colorado State University. Libraries, 2026)
The artist's statement: My work is rooted in storytelling, with every piece designed to communicate emotion, meaning, and ideas that extend beyond what is immediately visible. I aim to create visuals with purpose, where each composition carries a narrative and invites viewers to engage with its intent and message. As a graphic designer and traditional artist, I work across both digital and physical mediums using Adobe Creative Suite, Krita, and traditional materials such as graphite, ink wash, colored pencil, chalk, and pen. My process begins with rapid sketching with Sharpie or pencil, allowing me to freely explore concepts before refining stronger ideas through research, observation, and a deeper investigation of the subject and its context. I focus on clarity, color-theory, balanced compositions, and a strong visual focal point, often leaning toward clean, minimal, and realistic aesthetics. I am inspired by growth, creativity, and the discipline of continually improving my skills. I strive for versatility in style to allow each artistic approach to suit each project's needs, ensuring the outcome aligns with the concept and audience. As a designer, I prioritize the client's vision and goals, aiming to translate their ideas into intentional, effective, and visually engaging solutions. My work reflects a commitment to hard work, thoughtful problem-solving, and developing designs that are both meaningful and functional.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: graphic design